Cannabis use during pregnancy: Are we at the verge of defining a "fetal cannabis spectrum disorder"?. (March 2019) - Schreiber, S.; Pick, C.G.
Abstract: Cannabis is probably the drug most commonly used globally since ancient times. Following the trend of legalization of access to cannabis in several Western countries, its use has increased in North America over the past few years. In spite of warnings of the potential hazards associated with in-utero exposure to cannabis, approximately 10% of pregnant women in an American study reported using cannabis in recent years, and most of them on a daily basis. Significant effects of prenatal cannabis exposure have been found on children's sleep, cognitive functions (memory and scholastic skills), as well as on executive (frontal lobe) functions (reasoning, attention, impulsivity, and motivation), and affective (depression) and anxiety symptoms throughout the stages of development. Following the presentation of two case vignettes, we integrate the published information on outcomes of maternal use of cannabis during pregnancy on the developing fetus and the "soft" neurological deficits and neuro-behavioral disturbances manifested by them from early childhood and evolving to peaks in adolescence. Taken together, these data serve to define what we call a heretofore unspecified "fetal cannabis spectrum disorder".